Enhanced CO selectivity for reverse water‐gas shift reaction using Ti4O7‐doped SrCe0.9Y0.1O3‐δ hollow fibre membrane reactor - Zhuang, S.; Han, N.; Wang, T.; Meng, X.; Meng, B.; Li, Y.; Sunarso, J.; Liu, Shaomin (Wiley-Blackwell Publishing, 2019)
Reverse water-gas shift reaction (RWGS) is important in the CO2 utilization cycle to convert carbon dioxide (CO2) and hydrogen (H2) to carbon monoxide (CO). In this work, the RWGS performance is evaluated by utilizing Ti4O7-doped SrCe0.9Y0.1O3-d (SCY-b) hollow fibre membrane reactor where H2 permeates through the SCY-b proton conducting membrane and reacts with CO2 feed gas. Upon increasing the temperature from 750 to 950 °C, the CO yield increased from a negligible value to 14.82 %, when the sweep gas flow rate was 50 mL min-1 H2-He (50:50 vol. ratio) and the feed gas flow rate was 100 mL min-1 CO2-N2 (5:95 vol. ratio). The CO yield increase with the temperature increase reflects the enhanced H2 permeation flux through the SCY-b membrane at higher temperatures. Higher CO2 concentration in the feed gas led to lower CO yield due to the higher amount of remaining CO2 in the outlet stream. The deposition of porous SCY or SCY-b surface layer onto the hollow fibre outer circumference surface also increased H2 flux through the fibre relative to the non-deposited one. Thermogravimetric and CO2-temperature programmed desorption results further reveal that SCY-b adsorbed CO2 at temperature above 500 °C due to the reaction between CO2 and SCY-b material. Despite the formation of SrCO3 during RWGS, the SCY-b hollow fibre membrane reactor still displayed a stable CO yield of around 14 % throughout the 6-day continuous membrane reactor test.